Empowering Human-AI Collaboration in Air Traffic Control through Smart Interaction Design - Tyburzy, Lukas; Jameel, Mohsan; Hunger, Robert; Bohm, Julian (IEEE/AIAA Digital Avionics Systems Conference, 2024)
The growing number of aircraft movements and the increasing need to guide aircraft more efficiently while maintaining the highest safety standards heightens the complexity of the air traffic controller (ATCO) workspace. Air navigation service providers struggle to train enough staff to meet this higher demand and compensate for retirements. To address this challenge, the German Aerospace Center (DLR) is developing Single Controller Operations, which enables a single ATCO to handle traffic in a sector. This approach introduces the AI-based Digital Interactive Reliable Controller (DIRC), which collaborates with human ATCOs on air traffic control tasks, forming Human Autonomy Teaming (HAT). DIRC leverages several advanced digital tools to perform specific tasks traditionally managed by human ATCOs, such as conflict detection and resolution, and coordination of aircraft handovers. The integration of DIRC necessitates a novel human-machine interface (HMI) to ensure the human ATCO maintains situational awareness and can supervise and interact with DIRC effectively, rather than being overwhelmed by the additonal system handling and monitoring required for this high level of automation. This HMI, termed Human Interface to DIRC (HI-DIRC), was developed to facilitate interaction and build trust between human controllers and their digital counterparts. The HI-DIRC interface, inspired by electronic flight strip systems, is implemented on an additional display and offers an overview of aircraft under DIRC's control, along with a history of commands issued. It features interactive elements allowing the human ATCO to assume control from DIRC when necessary, and includes a request area where DIRC can seek approval for actions or transfer control of aircraft. This design aims to minimize information clutter and supports the human ATCO's decision-making processes by providing essential information in an accessible format. The paper presents the conceptualization, design, and and implementation of HI-DIRC, including task analysis and graphical interface wireframes. Feedback from ATCO workshops guided iterative improvements to ensure the interface supports effective HAT. Future validation efforts will involve further workshops and human-in-the-loop simulations to refine the integration of HI-DIRC into the ATCO workspace, enhancing the overall efficiency and safety of air traffic control operations.